Digitalizing midwifery education: Trends, tools, and transformation - Mona Melisa; Ari Indra Susanti (Curricula: Journal of Curriculum Development, 2025)
The development of digital technology has brought significant changes to the field of education, including midwifery education. The integration of technology into the learning process is believed to improve the quality of education and the competencies of midwifery students. This study aims to explore the use of technology in midwifery education and its impact on student learning outcomes. A scoping review was conducted using the PEO framework (Population, Exposure, Outcome), focusing on midwifery students, the use of technology, and learning effectiveness. Literature was collected from databases such as PubMed, ScienceDirect, and Google Scholar, using keywords related to technology implementation, learning effectiveness, and midwifery education. Articles were selected based on systematically defined inclusion and exclusion criteria. Descriptive analysis was used to identify key themes, types of technology applied, and their effects on the learning process. The findings indicate that e-learning, virtual reality, and artificial intelligence are the most commonly used technologies. These tools have been shown to enhance theoretical understanding, practical skills, and learning motivation. However, challenges such as limited access, insufficient faculty training, and unequal infrastructure remain. Therefore, well-planned and sustainable implementation strategies are needed to optimize the use of technology in midwifery education.   Abstrak Perkembangan teknologi digital telah membawa perubahan signifikan dalam dunia pendidikan, termasuk di bidang kebidanan. Integrasi teknologi dalam proses pembelajaran diyakini mampu meningkatkan mutu pendidikan dan kompetensi mahasiswa kebidanan. Studi ini bertujuan untuk mengeksplorasi pemanfaatan teknologi dalam pendidikan kebidanan dan dampaknya terhadap hasil belajar mahasiswa. Metode yang digunakan adalah tinjauan skoping dengan pendekatan PEO (Population, Exposure, Outcome) yang memfokuskan pada mahasiswa kebidanan, penggunaan teknologi, dan efektivitas pembelajaran. Literatur dikumpulkan dari basis data seperti PubMed, ScienceDirect, dan Google Scholar, menggunakan kata kunci yang berkaitan dengan implementasi teknologi efektivitas pembelajaran, dan pendidikan kebidanan. Artikel diseleksi berdasarkan kriteria inklusi dan eksklusi yang ditetapkan secara sistematis. Analisis deskriptif digunakan untuk mengidentifikasi tema utama, jenis teknologi yang digunakan, serta dampaknya terhadap proses pembelajaran. Hasil menunjukkan bahwa e-learning, realitas virtual, dan kecerdasan buatan merupakan teknologi yang paling sering digunakan. Ketiga teknologi ini terbukti meningkatkan pemahaman teoretis, keterampilan praktik, dan motivasi belajar mahasiswa. Namun, tantangan seperti keterbatasan akses, kurangnya pelatihan dosen, dan infrastruktur yang belum merata masih menjadi kendala. Oleh karena itu, diperlukan strategi implementasi yang terarah dan berkelanjutan agar teknologi dapat dimanfaatkan secara optimal dalam pendidikan kebidanan. Kata Kunci: implementasi; pendidikan kebidanan; teknologi